Ellipsen in der Jugendsprache in deutschen Jugendserien - Ciecharowska, Justyna (Die deutsche Sprache in vielfältigen Forschungsparadigmen. Beiträge polnischer Doktoranden anlässlich der 9. Linguistischen Tagung–Łódź, 09.05.2015, 2016)
The following article is an attempt to analyse the structure of the language used by teenagers in Germany and the role of the mass media in shaping it. The article focuses on ellipses – their frequency and type. The introduction aims at defining the youth language, spoken language, a film series and a youth film series as well as different categories of ellipses. The article focuses on the ellipses used in two youth film series Der Lehrer and Türkisch für Anfänger (425 examples). The conclusions are presented by categories: type of ellipses (general characteristics), syntactic and lexical ellipses (detailed characteristics) and the ratio of ellipses to the number of sentences. The analysis has proven that film dialogue scripts (the so called “artificial” language) have the same characteristics as the spoken language.